Strategies for Sustainable Tourism Development: A Case Study of Consumer Behavior in the Fast Fashion Retail Sector - Tan Lay Hong; Paul Dung Gadi; Syaza Udaimatunnur Safa Binti Ridzal Hef; Syed Isyraf Muzammil Bin Syed Hidzir; Tan Chia Joe; Tan Chia Yan; Tan Eiwins; A. J. Ali; Daisy Mui Hung Kee (International Journal of Tourism and Hospitality in Asia Pasific, 2025)
Uniqlo, a leading global fashion retailer, has gained popularity due to its affordability, quality, and brand identity. Understanding the key factors influencing consumer behavior is crucial for optimizing marketing strategies and customer engagement. This study examines the impact of psychological, social, cultural, economic, and personal factors on consumer purchasing behavior at Uniqlo. The objective of this research is to assess which of these factors significantly influence consumer decision-making. To achieve this, we conducted a survey and collected responses from 100 participants through Google Forms. The collected data were analyzed using multiple regression analysis to determine the relative impact of each factor. The results indicate that psychological (? = 0.275) and economic (? = 0.261) factors have the most substantial influence on consumer behavior, supporting H3 and H2, respectively. Social factors (? = 0.174) also play a significant role, affirming H1. However, cultural factors (? = 0.092) have a weaker influence, and personal factors (? = 0.008) show an almost negligible effect, rejecting H5. The model explains 41.6% of the variance in consumer behavior (R² = 0.416). These findings suggest that Uniqlo should focus on strengthening psychological and economic appeals in its branding and marketing strategies, emphasizing affordability, quality, and emotional connection to drive customer loyalty and engagement.